Taxonomy of High-Latitude Goniasteridae (Subantarctic & Antarctic): one new genus, and three new species with an overview and key to taxa - Mah, Christopher L. (Zootaxa, 2011)
A review of high-latitude Goniasteridae south of 50ºS is presented, including a key to species, figures and taxonomic descriptions of all species with a brief taxonomic summary for all genera. Nineteen species in 11 genera are reviewed. Eratosaster jenae nov. gen and sp., Chitonaster trangae nov. sp., and Pillsburiaster calvus nov. sp. are described. Several taxa, including Chitonaster, have not been reviewed since their initial description and revision of the group has clarified taxonomic boundaries between species. The genus Pentoplia is a junior synonym of Chitonaster. Rarely encountered species, synonyms, and range extensions are reported for multiple species.